2012
DOI: 10.1016/j.tiv.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of cigarette smoke extract and ambient ultrafine particles on endothelial cells

Abstract: Previous studies have shown that ambient ultrafine particles with diameters less than 100 nm (UFPs) can pass from the lungs to the circulation because of their very small diameter, and induce lung oxidative stress with a resultant dysfunction of lung endothelial cells. However, no studies have addressed the potential combined effects of UFPs and cigarette smoke on vascular endothelial cells. We hypothesized that co-exposure to UFPs and cigarette smoke extract (CSE) may cause combined effects on activation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
(97 reference statements)
1
26
0
Order By: Relevance
“…Active smoking is widely recognised as one of the major causes of coronary artery disease, cancer (particularly lung cancer), and chronic obstructive pulmonary disease in adults (USDHHS, 2006), as well as impacting the function of the endothelium and causing altered gene expression in endothelial cells via their ability to generate ROS and nitrogen species (Bercher et al, 2007;Mo et al, 2012). Insoluble nanoparticles are capable of translocation from the lung to other parts such as the lymph nodes, spleen, heart and bone marrow; their high surface to mass ratio increases biological activity relative to larger particles of the same chemical composition (Oberdörster et al, 2005;Kreyling et al, 2010).…”
Section: Cigarette Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active smoking is widely recognised as one of the major causes of coronary artery disease, cancer (particularly lung cancer), and chronic obstructive pulmonary disease in adults (USDHHS, 2006), as well as impacting the function of the endothelium and causing altered gene expression in endothelial cells via their ability to generate ROS and nitrogen species (Bercher et al, 2007;Mo et al, 2012). Insoluble nanoparticles are capable of translocation from the lung to other parts such as the lymph nodes, spleen, heart and bone marrow; their high surface to mass ratio increases biological activity relative to larger particles of the same chemical composition (Oberdörster et al, 2005;Kreyling et al, 2010).…”
Section: Cigarette Emissionsmentioning
confidence: 99%
“…Insoluble nanoparticles are capable of translocation from the lung to other parts such as the lymph nodes, spleen, heart and bone marrow; their high surface to mass ratio increases biological activity relative to larger particles of the same chemical composition (Oberdörster et al, 2005;Kreyling et al, 2010). Recent research indicate that co-exposure to ambient nanoparticles and cigarette smoke extract causes enhanced injury to endothelial cells and may cause combined effects on activation of endothelial cells and dysfunction of the endothelium by oxidative stress through activation of NADPH oxidase (Mo et al, 2012). However, there are so far no studies available which have apportioned the effect of cigarette derived nanoparticle exposure from effects caused by other ambient nanoparticles.…”
Section: Cigarette Emissionsmentioning
confidence: 99%
“…The same batch of PBS, but which had not been smoke-bubbled, was used as control. CSE was aliquoted and stored at À80°C until required for use [10,11].…”
Section: Generation Of Cigarette Smoke Extractmentioning
confidence: 99%
“…Mitochondrial ROS has been implicated in inflammatory cytokine production, providing a possible link between ROS-driven and inflammatory diseases [32]. Studies in cultured human cells have shown that exposure to particulate matter increases mitochondrial ROS [33][35], and these mitochondrial ROS increases cause increased IL-6 gene expression [34], [35]. Conversely, inhibition of mitochondrial ROS reduces inflammatory cytokine production in response to inflammatory stimulus [36].…”
Section: Discussionmentioning
confidence: 99%